Penerapan Business Model Canvas (BMC): Petani Muda Kelapa Sawit Jambi - Anaseputri Jamira; Fachruddin Razi; Yulita Febriani (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study is to apply the Business Model Canvas (BMC) to the business of oil palm farmers owned by young people in Jambi Province. This study used qualitative research methods through a descriptive approach and case studies. The analytical tool in this study used the Business Model Canvas (BMC). An in-depth analysis is carried out on business activities and the environment. The research sample amounted to 5 people determined by the purposive sampling method. Primary data was obtained through surveys, observations, and interviews, while secondary data was obtained through literature review. The results of the analysis with 9 components of BMC show that in general, oil palm farmers experience limited resources in plantation management to the selling process. The business development strategy that can be carried out is to look for Key Partners to support all fulfillment of the limited resources of Farmers in running a plantation business in a better and optimal manner. Key Partners in the form of “Support System” can be found or formed with the help of other parties. Synergistic Government, Companies, Educational Institutions (GCE) are needed, both at the policy level, as well as technically in an applicable and sustainable manner. The future research can be developed into qualitative and quantitative research, on different objects, with more complex models, involving more than one general business strategy development method such as SWOT Analysis and Blue Ocean Strategy, to marketing strategy, marketing mix, and promotion mix. for more in-depth and complex analysis.